EFEKTIVITAS SISTEM AI DALAM MEREDUKSI BEBAN ADMINISTRATIF PENDIDIK DAN MENINGKATKAN AKURASI EVALUASI PEMBELAJARAN: SYSTEMATIC LITERATURE REVIEW - Ramadhan, Laili; Yanuarita Sutikno, Putri; Wijayati, Nanik; Avrilianda, Decky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Administrative overload constitutes an acute structural challenge faced by Indonesian elementary school (SD) teachers implementing the Merdeka Curriculum. This study analyzes the effectiveness of an AI-based system integrating QR Code technology, the Gemini generative AI model, and the Supabase cloud database as a holistic solution, employing a PRISMA-guided Systematic Literature Review (SLR) methodology. Of 312 identified articles, 25 high-quality studies were included following multi-stage screening. Synthesis reveals that: (1) integrated AI systems can reduce assessment administration duration by 60–80%; (2) QR Code technology eliminates student misidentification errors; and (3) generative AI achieves substantial inter-rater agreement (κ ≥ 0.61) for essay response evaluation. These findings underscore the urgency of integrating AI administrative systems specifically designed for Indonesian elementary school contexts to support Merdeka Curriculum implementation.